PERSEPSI KEPUASAN PASIEN PADA KUALITAS PELAYANAN DI RUMAH SAKIT GIGI DAN MULUT UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Inna Sholihati Embrik; Siti Dyah Handayani; Mohammad Syafril Nusyirwan (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2013)
Dental Hospital, University of Muhammadiyah Yogyakarta is a teaching hospital whose role is a Muhammadiyah unit businesses engaged in the service sector. In dealing with the increasing level of competitions among hospitals, the hospital is always competing to attract that customers to keep loyal to choose the service given. The quality of health care is a factor that can increase patient satisfaction. The quality of service is the totality of the rorm of the characteritics of the goods or service that show the ability to satisfy customer need, both obvious and hidden. Objective of the research To investigate the perception of patient satisfaction on the quality of service in the Dental Hospital, University of Muhammadiyah Yogyakarta. The study is quantitative research. The sample used as many as 100 people. The research instrument used was questionnaire. The analysis of the data is by using descriptive statistical analysis, factor analysis, and differenting test (t-test and anova). The results showed that patient satisfaction perceptions of the quality of service in terms of five dimensions expressing great satisfaction by 77% and 23% expressed satisfaction. The dimensional factor of direct evidence (tangible) is the most important factor that can increase patient satisfaction. Conclusion, the perception of patient satisfaction on the quality of service in the Dental Hospital, University of Muhammadiyah Yogyakarta consisting of tangibility, empathy, reliability, assurance, and responsiveness showed that the level of satisfaction is in the high category (very satisfied).